Comparison of Bone Mineral Density in Patients with Celiac Disease and Healthy Individuals - Roymon Joseph1, Ranjna Janagal2 , Mohan Singh3, Dimple Patel4, Rohit Zariwala5 Garima Khatri6 , Khus (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: To study the effects of celiac disease on bone mineral density.Design: Case-control study.Setting: The study was conducted in Department of Anatomy, Sardar Patel Medical College, Bikaner,Rajasthan.Participants: A total of 90 patients, 60 control group healthy normal and 30 celiac disease patients casegroup were incorporated in study with informed consent.Material and Methods: The bone mineral density was measured in case and control group at calcaneum byperipheral dual X-ray absorptiometry along with body mass index and age.Results: The significant difference was found between the bone mineral density of case and control group(0.87±0.49 & 0.61±0.44: p=0.0001) and 43.33% subjects had osteopenia in case group while only 5% subjectshad osteopenia in healthy group. The significant difference of bone mineral density in both groups below theage of 15 years was non existing but between the age group of 16-30 years it was significant(-1.17±0.68 &0.68±0.21: p=0.001)Conclusion: Celiac disease patients are at higher risk of osteopenia so it is suggested that they should beinvestigated in early time of diagnosis mainly in the growing years because it affects most at this time.